Panax quinquefolius L. Saponins Protect Myocardial Ischemia Reperfusion No-Reflow Through Inhibiting the Activation of NLRP3 Inflammasome via TLR4/MyD88/NF-κB Signaling Pathway - Ping Yu; Yuangeng Li; Wenwen Fu; Xin Li; Yanzhe Liu; Yaozhen Wang; Xiaofeng Yu; Huali Xu; Dayun Sui (Frontiers Media S.A., 2021)
At present, many patients who undergo reperfusion immediately after percutaneous coronary intervention will undergo microvascular obstruction and reduction in myocardial blood flow. This phenomenon is called "no-reflow (NR)," and there is still no effective therapy for NR. Studies showed Panax quinquefolius L. saponins (PQS) have effect on MI/R injury, while the effect and mechanism of PQS on MI/R induced NR are not clear. In this study, we established a MI/R model to investigate whether PQS decrease NR phenomenon via suppression of inflammation. We found that PQS significantly alleviated the symptoms of NR by reducing ischemia, infarction, and NR area; improving cardiac function; preventing pathological morphology changes of myocardium; depressing leukocytes' aggregation and adhesion; and suppressing the excessive inflammation. Further study demonstrated that PQS remarkably inhibited TLR4, MyD88, p-NF-κB, and NLRP3 inflammasome-associated protein, and these effects could be reversed by LPS. These results indicated that PQS may protect NR by inhibiting the activation of NLRP3 inflammasome via TLR4/MyD88/NF-κB signaling pathway in part, suggesting that PQS exist potential in preventing NR induced by MI/R.